2004
DOI: 10.2307/4128620
|View full text |Cite
|
Sign up to set email alerts
|

Early Roman Mosaic Materials in Southern Britain, with Particular Reference to Silchester (Calleva Atrebatum): A Regional Geological Perspective

Abstract: Mosaics represent one of the best known art forms in the Roman world. Their geometric patterns and designs, their figurative images, and their development through time have been extensively studied, and corpora have been assembled for certain provinces of the Empire. In Britain, the study of the surviving mosaics has led to the identification of certain late Roman ‘schools’ (stylistic groupings) of mosaics on the basis of shared stylistic attributes. Now it will be possible to place this work in a fuller conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…phase (Allen and Fulford ry87, z8z;Fulford et al 1994, r94;Allen ;99B;zoq). Just one small port has been identified in the larer Roman period around the estuary -at Crandon Bridge on the river Parrett ( Figure 6) -and this appears to have functioned as a transhipment port on the Roman military authorities' supply route from Poole Harbour in south-east Dorset to south-east \fales via llchester (Allen and Fulford D96;zoo4;Rippon 1997, ,4). Vhile it could be argued that other sites lay unidentified, or have been lost to erosion, the artefactual evidence simply does noi suggest a large volume of cross-channel trade.…”
Section: T/te T/tamesmentioning
confidence: 99%
“…phase (Allen and Fulford ry87, z8z;Fulford et al 1994, r94;Allen ;99B;zoq). Just one small port has been identified in the larer Roman period around the estuary -at Crandon Bridge on the river Parrett ( Figure 6) -and this appears to have functioned as a transhipment port on the Roman military authorities' supply route from Poole Harbour in south-east Dorset to south-east \fales via llchester (Allen and Fulford D96;zoo4;Rippon 1997, ,4). Vhile it could be argued that other sites lay unidentified, or have been lost to erosion, the artefactual evidence simply does noi suggest a large volume of cross-channel trade.…”
Section: T/te T/tamesmentioning
confidence: 99%
“…The samples did not yield useful organic-walled microfossils. In contrast, tesserae sourced from clay-rich rock sequences (Allen & Fulford 2004) are known to yield useful palynological data.…”
Section: Methods For Recovering Microfossilsmentioning
confidence: 99%
“…Although other sources of chalk in southern England were clearly being exploited by the Romans, the addition of chalk to the range of stone types exploited in the Isle of Purbeck and then distributed considerable distances for employment elsewhere, gives further weight to the importance of that area and its associated manufacturing sites, like Norden, for the provision of materials for making mosaics and other decorative building materials from the later first century AD onwards (cf. Allen & Fulford 2004;Allen et al 2007). …”
Section: Geographical Provenance Of the Chalk Tesserae At Silchestermentioning
confidence: 99%
See 1 more Smart Citation
“…Founded in the late first century BC, the Romano‐British town of Silchester ( Calleva Atrebatum ) was an active participant in these developments. An extensive and ongoing area excavation at Insula IX within the walls has revealed that a range of Kimmeridgian rock‐types from Dorset were used for mosaics in the early Roman settlement (Allen and Fulford 2004). An especially distinctive component is a richly fossiliferous shale burnt to a dark red colour.…”
Section: Introductionmentioning
confidence: 99%